Distributian of Depth and Clay-Silt to Sand Ratio of Land Subsidence in Coastal Semarang City by Resistivity Methods - Sugeng Widada; Muhammad Zainuri; Gatot Yulianto; Sidhi Saputra; Baskoro Rochaddi (Jurnal Kelautan Tropis, 2019)
Semarang City is the capital of Central Java province, located in the northern coast of Java island, Indonesia which is geologically composed of alluvial deposits. The natural consolidation of young alluvial deposits has caused a land subsidence. On the other hand, load of buildings and constructions causes an increase in the pressure of land surface, and finally, leads to an increase in the rate of land subsidence. The drilling data indicated that not all layers of lithology are soft layers supporting the land subsidence. A research  on the depth of soft litology and its percentage of hard lithology has not been conducted ever before. On the other side, an analysis regarding this kind of  research can be conducted based on resistivity method. Sounding system method with Schlumberger electrode configuration was selected for field data collection. The goals of this research were to  determine  the  resitivity of  lithology so that it can be used to interpretate distribution of depth  and clay-silt  to sand ratio of land subsidence area. The results showed that the area with  the depth of the upper layer of clay-silt   less than  3  m and clay-silt  to sand ratio less than  4   were the high land subsidence area.